Cicatricial organising pneumonia associated with fibrosing interstitial pneumonia – a clinicopathological study. Issue 2 (4th November 2021) - Zaizen, Yoshiaki; Tabata, Kazuhiro; Yamano, Yasuhiko; Takei, Reoto; Kataoka, Kensuke; Shiraki, Akira; Nishimura, Koichi; Furuyama, Kazuto; Bychkov, Andrey; Hoshino, Tomoaki; Johkoh, Takeshi; Kondoh, Yasuhiro; et al.
Abstract : Aims: The recent recognition of cicatricial organising pneumonia (ciOP) indicates that the ciOP may resemble or simulate fibrotic interstitial pneumonia; however, there has been great uncertainty regarding the affected populations, pathogenesis, clinical relevance and characteristics. In this study, we compared the characteristics of fibrotic interstitial pneumonia with and without ciOP. Methods and results: We enrolled 121 patients from the consultation archive whose pathological findings were fibrotic interstitial pneumonia and for whom follow‐up clinical data were available. We reviewed these cases histopathologically and classified them according to whether or not they showed ciOP. We compared the clinicopathological features between the two groups. CiOP, histopathologically characterised by deposition of dense collagenous fibres within the alveolar space without destruction of the lung structure, was found in 48 patients (39.7%). None of the cases with ciOP experienced acute exacerbation during 12 months' follow‐up. The group with ciOP had more severe diffusion impairment but this, together with restrictive ventilatory impairment, improved significantly compared to the group without ciOP. Conclusion: CiOP is a histopathological finding commonly found in fibrotic interstitial pneumonia. It does not relate to acute exacerbation or decrease in pulmonary function. Abstract :